Robert Drew and the development of cinema verite in America - O'Connell, P. J., 1935-2006 (Southern Illinois University Press, 2010)
Author P.J. O'Connell traces Robert Drew's influence on cinema verite through extensive interviews with Drew and with some of the founding fathers of American cinema verite filmmaking-Donn Alan Pennebaker, Gregory Shuker, and Richard Leacock. Robert Drew's contributions to documentary film have been both technical and conceptual. Realizing that his equipment was too heavy and intrusive, Drew persuaded Time-Life Broadcasting to sponsor the development of new, lightweight, portable synchronous sound equipment that freed documentary filmmakers from the bulky, tripod-moun.